Predictors of Undiagnosed and Uncontrolled Hypertension in the Local Community of Byblos, Lebanon - Hazar Kanj; Ali Khalil; Mikhael Kossaify; Antoine Kossaify (SAGE Publishing, 2018)
Objective: This study aimed to determine the prevalence and predictors of undiagnosed and uncontrolled hypertension (HTN) in a local community in Lebanon. Design and methods: In this cross-sectional study, we interviewed 911 adults in the local community of Byblos, Lebanon, and 691 were enrolled in the study. Blood pressure (BP), height, and weight were measured. The diagnosis of HTN was based on the 2013 European Society of Hypertension (ESH)/ European Society of Cardiology (ESC) guidelines (systolic BP ⩾140 mm Hg and/or diastolic BP ⩾90 mm Hg). The data collected were analyzed using "Statistical Package for the Social Sciences" software (SPSS). Results: A total of 260 participants were found to be hypertensive, either previously diagnosed or undiagnosed, yielding an overall prevalence of HTN of 37.62%. Of these participants, 149 (57.31%) were previously diagnosed and had controlled BP, and 111 (42.69%) had undiagnosed or uncontrolled HTN. Of these 111 participants, 44 had undiagnosed HTN and 67 were previously documented as hypertensive but had uncontrolled BP. Younger age and the absence of associated cardiovascular comorbidities were found to be associated with undiagnosed HTN, whereas high body mass index, smoking, and nonadherence to therapy were found to be associated with uncontrolled HTN. Conclusion and implications: This study revealed a relatively high prevalence of HTN in the studied population, along with a high prevalence of undiagnosed and uncontrolled HTN. These findings emphasize the need for wider and more efficient screening strategies to better diagnose and control HTN in the general population.